UK households' carbon footprint: A comparison of the association between household characteristics and emissions from home energy, transport and other goods and services - Milena Buchs; Sylke V. Schnepf (Institute for the Study of Labor (IZA), 2013)
Does the association between household characteristics and household CO2 emissions differ for different areas such as home energy, transport, indirect and total emissions in the UK? Specific types of households might be more likely to have high emissions in some areas than in others and thus be affected differently by climate mitigation policies that target these areas. Using the Living Costs and Food Survey and Expenditure and Food Survey for the years 2006 to 2009, this paper compares how household characteristics like income, household size, rural/urban location and education level differ in their association with home energy, transport, indirect and total emissions. We find that the association between household characteristics and emissions differs considerably across these areas, particularly for income, education, the presence of children, female headed, workless and rural households. We also test the implicit assumption in the literature that the association between household characteristics and CO2 emission is constant across the CO2 emission distribution using quantile regressions and compare results for poor and rich households. The analysis considers policy implications of these findings throughout.
Keywords: D12; D31; D60; H20; Q01; 330; carbon dioxide emissions; inequality; climate change mitigation policies; living costs and food survey; United Kingdom